PENGARUH SIKAP KONSUMEN TENTANG PENERAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP LOYALITAS KONSUMEN PASTA GIGI PEPSODENT PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA - pasri y pasaribu (Universitas Sumatera Utara, 2013)
The aim of research is to understand and analyze the influence of consumer behaviour about the implementation in Corporate Social Responsibility program in loyalty Pepsodent tooth paste consumer.The research method which used to analyze the influence of consumer behavior in using Corporate Social Responsibility program in loyalty Pepsodent tooth paste consumer are descriptive Analysis and regresi linier plural method.The population in the research are overall of student in S-1 Program at the conscripts of 2009-2011 class of Public Health Faculty student in Sumatera Utara University which amount 447 students. The sample which used in this research is about 82 students. The sample measure in this research decide with Slovin formula. The writer used sampling random sample method, with sample rule is the student must used the Pepsodent at least 3 months.The result of Simultan Significant Test (Test F) show that variable of consumer behavior in using Corporate Social Responsibility program which consist of variable likes cognitive component, affective component, conative component in simultant influenced signify in loyalty Pepsodent tooth paste consumer at Public Health Faculty student in Sumatera Utara University. The result of Parcial Test (Test-t) behavior variable which consist of variable likescognitive component, affective component, conative component have positive influenced and signify in in loyalty Pepsodent tooth paste consumer at Public Health Faculty student in Sumatera Utara University. The conative component behavior variable influence more dominant than cognitive component and affective component.Key words : cognitive, affective, conative, loyalty consumer.